Workers' satisfaction with health surveillance: Development and validation of a new scale - Adrián Fernández-del-Peral; Javier González-Caballero; Ángel Pérez-Navarro; María-Antonia Ruiz-Olmedo; Juan-Pedro Castillo-Córdoba; María-del-Carmen Gallego-Peragón; Manuel Romero-Saldaña (International Journal of Nursing Studies Advances)
Background: Health surveillance in the workplace involves conducting occupational health examinations of workers based on the risks to which they are exposed. The objective is to protect their health and proactively identify potential harm resulting from occupational activities. However, there is no assessment tool which focuses on workers' satisfaction with this activity. Therefore, having a validated instrument for measuring workers' satisfaction with health surveillance would enable the optimization of the care provided in occupational health services through a continuous improvement process. Objective: To develop and validate a questionnaire to assess the satisfaction of the working population with health surveillance. Design: A cross-sectional psychometric validation study. Setting: Data were collected from an occupational health service in Spain. Participants: A total of 600 participants were included, selected by convenience sampling. Methods:: The research was carried out in four phases: i) Design review and selection of the questionnaire items. ii) Content validation: participation of a group of 12 experts, using Delphi methodology. iii) Pilot study: running a pilot study (n = 30 workers). iv) Construct validation: with a sample of 600 workers, performing an exploratory factor analysis (EFA) and confirmatory factor analysis (CFA), both on sample of 300 workers. Results: The final version of the scale comprised 17 items distributed in 4 factors, explaining 63.4 % of the total variance. Content validity (Aiken's V coefficient = 0.904, Lawshe's content validity index = 0.868) and construct validity (Cronbach’s alpha = 0.870, McDonald's omega = 0.872, intraclass correlation coefficient = 0.861) were demonstrated. The factors obtained in the EFA with half of the sample were confirmed in the other half, with the CFA indices suggesting an acceptable model fit. Conclusions: The psychometric properties showed a valid, reliable instrument to assess workers' satisfaction with health surveillance. It is therefore a useful tool for occupational health professionals and can improve the care provided to workers.